MEMBANGUN PENDIDIKAN KARAKTER YANG TOLERAN DAN BIJAKSANA MELALUI PEMAHAMAN HADIS - Novi Anggriani Fitri; Muhid Muhid (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
Character education is the main foundation in forming a young generation that is not only intellectually intelligent, but also has noble, tolerant, and wise morals amidst the currents of globalization and complex social problems. The Hadith of the Prophet Muhammad SAW has great potential as a source of values ​​and guidelines in building a tolerant and wise character, but its utilization has not been optimal. This study aims to examine and implement relevant hadiths to formulate an effective character education model. Through a literature study, this article discusses the relevance of hadiths in character education, especially the value of honesty (Ash-Shidq) which leads to goodness and heaven, as well as the character of tolerance and compassion (At-Tasamuh Wal Rahmah) which encourages empathy and creates an inclusive environment. In addition, the character of responsibility and trustworthiness, which emphasizes each individual as a leader of what they lead, is an important foundation. The implementation of ideal character education requires a holistic environment, an integrated curriculum, school-family-community collaboration, and the role of teachers as role models. However, challenges such as limited teacher understanding, academic pressure, negative environmental influences, and shifts in socio-cultural values ​​often hinder effective implementation. Therefore, character education must be adaptive, balancing traditional and modern values, and requires collaborative support from various parties to create a generation with integrity, adaptability, and the ability to bring about positive change.